A model of event-destination image transfer - Deng, Qian; Li, Mimi (My University, 2014)
The aim of this study is to provide a theoretical understanding and empirical examination of the psychological responses of tourists attending a mega-event hosted in a tourism destination. A conceptual framework—the event–destination image transfer model—was developed from an extensive literature review and related theoretical discussion. A survey was conducted in Shanghai during the 2010 Shanghai World Expo to test the model. The findings show that the event image directly and positively affected the destination image, providing empirical support for the image transfer theory. Tourists’ psychological responses—their overall attitude and behavioral intentions toward the destination—were positively and significantly affected by the destination image. However, the direct effect of the event image on tourists’ overall attitude toward the destination was statistically non-significant due to the mediation effect of the destination image.
Keywords: image transfer; event image; destination image; attitude; behavioral intentions; structural equation modeling